Towards a UV completion of chameleons in string theory - Hinterbichler, Kurt; Khoury, Justin; Nastase, Horatiu [UNESP] (Springer, 2011)
Chameleons are scalar fields that couple directly to ordinary matter with gravitational strength, but which nevertheless evade the stringent constraints on tests of gravity because of properties they acquire in the presence of high ambient matter density. Chameleon theories were originally constructed in a bottom-up, phenomenological fashion, with potentials and matter couplings designed to hide the scalar from experiments. In this paper, we attempt to embed the chameleon scenario within string compactifications, thus UV completing the scenario. We look for stabilized potentials that can realize a screening mechanism, and we find that the volume modulus rather generically works as a chameleon, and in fact the supersymmetric potential used by Kachru, Kallosh, Linde and Trivedi (KKLT) is an example of this type. We consider all constraints from tests of gravity, allowing us to put experimental constraints on the KKLT parameters.
Keywords: Strings and branes phenomenology